An updated radiosynthesis of [18F]AV1451 for tau PET imaging - Andrew V. Mossine; Allen F. Brooks; Bradford D. Henderson; Brian G. Hockley; Kirk A. Frey; Peter J. H. Scott (SpringerOpen, 2017)
Abstract Background [18F]AV1451 is a commonly used radiotracer for imaging tau deposits in Alzheimer's disease (AD) and related non-AD tauopathies. Existing radiosyntheses of [18F]AV1451 require complex purifications to provide doses suitable for use in clinical imaging studies. To address this issue, we have modified the synthesis of [18F]AV1451 to use only 0.5 mg precursor, optimized the Boc-deprotection step and developed a simplified method for HPLC purification of the radiotracer. Results An optimized [18F]AV1451 synthesis using a TRACERLab FXFN module led to high radiochemical yield (202 ± 57 mCi per synthesis) and doses with excellent radiochemical purity (98 ± 1%) and good specific activity (2521 ± 623 Ci/mmol). Conclusion An updated and operationally simple synthesis of [18F]AV1451 has been developed that is fully automated and prepares radiotracer doses suitable for use in clinical tau PET studies.